Pembelajaran Tahfidzh Alqur’an sebagai Upaya Penguatan Identitas Keagamaan Siswa di Madrasah Aliyah Tahfizhul Qur’an Raudhatul Mufassirin Indonesia - Suriyani Imah Hasibuan; Yulia Rahman (YASIN, 2026)
Tahfidz Al-Qur’an instruction has been widely studied in relation to the development of students’ religious character. However, studies specifically examining its role in strengthening students’ religious identity at Madrasah Aliyah Tahfizhul Qur’an Raudhatul Mufassirin Indonesia remain limited. This study aimed to analyze the implementation of tahfidz Al-Qur’an instruction and its contribution to strengthening students’ religious identity. This study employed a qualitative approach with a case study design. The informants comprised a tahfidz teacher, the head of the madrasah, and students who were purposively selected. Data were collected through observation, interviews, and documentation and subsequently analyzed through data reduction, data presentation, and conclusion drawing. Data trustworthiness was strengthened through source and method triangulation. The results showed that tahfidz instruction was implemented systematically through recitation improvement, application of the Ummi method, memorization, muroja’ah, memorization recitation, and evaluation. This instruction contributed to strengthening students’ religious identity, as reflected in doctrinal beliefs, regular religious observance, participation in socio-religious activities, the internalization of ethical values and Islamic behavior, and personal spiritual experiences. These findings emphasize that tahfidz instruction is oriented not only toward memorization achievement but also toward the comprehensive development of students’ religious identity. This study provides a practical contribution for madrasahs in developing tahfidz programs that integrate memorization, religious habituation, behavioral development, and spiritual experience. Future research should expand the research settings and employ mixed-methods approaches or longitudinal designs to obtain a more comprehensive understanding of the development of students’ religious identity.